Functional Roles of Astrocyte Calcium Elevations: From Synapses to Behavior - Guerra-Gomes, Sónia; Sousa, Nuno; Pinto, Luísa; Oliveira, João F. (Frontiers in Cellular Neuroscience, 2018)
Astrocytes are fundamental players in the regulation of synaptic transmission and plasticity. They display unique morphological and phenotypical features that allow to monitor and dynamically respond to changes. One of the hallmarks of the astrocytic response is the generation of calcium elevations, which further affect downstream cellular processes. Technical advances in the field have allowed to spatially and temporally quantify and qualify these elevations. However, the impact on brain function remains poorly understood. In this review, we discuss evidences of the functional impact of heterogeneous astrocytic calcium events in several brain regions, and their consequences in synapses, circuits and behavior.